Formulation and characterisation of biocompatible nanoparticles as therapeutic carriers in pulmonary delivery. - Tan, Yi Ping. (2009)
This project aimed to characterize PCL and PMMA nanoparticles for the benefit of pulmonary delivery. Characterization of PCL and PMMA nanoparticles were done mainly on the formulation of water-organic solvent ratio. The process of forming nanoparticles from polymer is the solvent displacement method. A range of water-acetone ratio and surfactant concentration were varied in the first part of the experiment for PCL nanoparticles and the water-acetone ratio range was narrowed for the second part of the experiment, conducted at two different initial PCL concentrations (mg PCL/ ml of acetone). For the third part of the experiment, two water-acetone ratios and two initial PCL concentrations were selected and used for another round of PCL nanoparticles characterization. PMMA synthesis was done in the first part of the experiment by varying water-ethanol ratio. Nanoparticles size, yield and drug loading content are known to be affected by protocol variables such as the water-organic solvent ratio. It was found out that PCL nanoparticles size decreases and yield increases with increasing water-acetone ratio while PMMA nanoparticles size and yield increase with increasing water-ethanol ratio. Also, at relatively lower initial PCL concentration, over a range of water-acetone ratios, nanoparticles are smaller in size and better in yield.